Single‐egg comet assay: A protocol to quantify DNA damage in natural bioarchives - Rejin Salimraj; Alessio Perotti; Marcin W. Wojewodzic; Dagmar Frisch (Methods in Ecology and Evolution)
Abstract The comet assay (CA), originally developed as toxicity test, quantifies DNA integrity from DNA distribution across an electric field. Compromised DNA moves across electric fields faster than intact DNA strands, leaving quantifiable signatures that resemble comet tails. Comet tail dimensions reflect relative DNA damage. We optimised the CA protocol for individual dormant propagules (single‐egg comet assay or SE‐CA) to inform downstream analyses such as DNA sequencing of the DNA quality contained in natural genetic archives of past populations. As a model, we used dormant eggs of the microcrustacean Daphnia. We evaluated the feasibility of the SE‐CA protocol to quantify DNA damage caused by processing and storage conditions for dormant eggs and in dormant eggs retrieved from recently deposited to centuries‐old lake sediment. In conclusion, our protocol provides a cost‐effective method of assessing DNA damage in sedimentary propagules such as dormant Daphnia eggs. More generally, the SE‐CA is applicable to testing DNA integrity in individual propagules prior to genome sequencing or to quantify environmental impacts on natural sedimentary biobanks.